2009
DOI: 10.1007/s10534-009-9253-0
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxamate siderophores of Scedosporium apiospermum

Abstract: Scedosporium apiospermum is an emerging pathogen colonizing the airways of patients with cystic fibrosis and causing severe infections in immunocompromised hosts. In order to improve our knowledge on the pathogenic mechanisms of this fungus, we investigated the production of siderophores. Cultivation on CAS medium and specific assays for different classes of siderophores suggested the secretion of hydroxamates. A maximal production was obtained by cultivation of the fungus at alkaline pH in an iron-restricted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…However, after the increase in oxalic acid, we observed a decrease in its synthesis, as for catecholate and hydroxamate derivates. Acidic pH results in the reduced accumulation of siderophores (Bertrand et al 2009). Moreover, Williams et al (2011) have shown that reducing conditions in the cell generated by oxalate correlate with inhibition of the host oxidative burst and other defense responses.…”
Section: Discussionmentioning
confidence: 99%
“…However, after the increase in oxalic acid, we observed a decrease in its synthesis, as for catecholate and hydroxamate derivates. Acidic pH results in the reduced accumulation of siderophores (Bertrand et al 2009). Moreover, Williams et al (2011) have shown that reducing conditions in the cell generated by oxalate correlate with inhibition of the host oxidative burst and other defense responses.…”
Section: Discussionmentioning
confidence: 99%
“…Interesting applications of fungal siderophores have been reported recently, both in vitro and in clinical cases (43). Siderophores are secreted under iron stress to scavenge iron from host proteins like transferrin or ferritin (44).…”
Section: Low-molecular Weight Fungal Molecules Used In Vitro and In Vivomentioning
confidence: 99%
“…These fungi are capable to chronically colonize the CF airways (Borghi et al 2010;Zouhair et al 2013) suggesting pathogenic mechanisms allowing them to grow and multiply in the respiratory tract. Nevertheless, very few biochemical studies, focused on polysaccharides (a-glucans, rhamnomannans, and peptidorhamnomannans [PRMs]) ), glycolipids (glucosylceramides) (Pinto et al 2002), and siderophores (Bertrand et al 2009), have been performed so far regarding species of the S. apiospermum complex. In addition, hydrolytic enzymes thought to be involved in the host tissue invasion by the degradation of host protein barriers such as serine proteases (Larcher et al 1996), metalloproteases (Pereira et al 2009;Silva et al 2011), and phosphatases (Kiffer-Moreira et al 2007) have been identified, as well as enzymes possibly involved in evading the host oxidative response such as a cytosolic Cu,Zn-superoxide dismutase (SOD) (Lima et al 2007).…”
Section: Introductionmentioning
confidence: 99%